Prevalence of burnout syndrome and associated factors in biomedicals in the metropolitan region of Salvador, BA (Research, Society and Development, 2022)
Introduction: Burnout syndrome (BS) is a phenomenon characterized by chronic emotional exhaustion that can generate physical and psychological consequences. The presence of BS is reported in several health professionals. However, the literature lacks studies that investigate the prevalence of BS in biomedical professionals. Objective: The present study aimed to investigate the prevalence of BS and its associated factors in working biomedical practitioners in the metropolitan region of Salvador. Methods: To determine emotional exhaustion in biomedical professionals, a questionnaire adapted from the Maslach Burnout Inventory was applied, considered the gold standard in the detection of BS. Furthermore, a sociodemographic questionnaire was used to identify variables associated with the development of BS. Subsequently, the data were compiled in Excel and statistical analyzes were performed in the GraphPad Prism program. Results: The population studied was predominantly composed of women (67.3%), aged over 30 years (54.8%), single (67.3%), without children (66.3%), working in only one institution (54.8%), working 40 hours a week or less (57.7%), with remuneration of 1 to 3 minimum wages (43.3%) and who considered the working conditions adequate (81.7%). In this context, BS was identified in 42.3% of the participants (n=44), with single biomedicals identified as a more susceptible group. Conclusion: Based on the data presented, it is possible to conclude that the prevalence of BS in biomedical professionals is high, making it necessary to develop public policies aimed at combating the development of BS in this class of professionals.